PENGARUH PENGGUNAAN TEPUNG LABU KUNING (CUCURBITA MOSCHATA DURCH) TERHADAP KARAKTERISTIK CHIFFON CAKE BERBAHAN DASAR MODIFIED CASSAVA FLOUR (MOCAF) - Biandari Devi Permatasari, Komang; Timur Ina, Putu; Yusa, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
The purpose of this research is to know the effect of pumpkin flour and ratio mocaf on the characteristics of chiffon cake and to know the right ratio for pumpkin flour and mocaf to produce chiffon cake with the best characteristics. The experimental design used is randomized block design with the treatment ratio of pumpkin flour with mocaf 10% : 90%; 20% : 80%; 30% : 70%; 40% : 60%; 50% : 50%; and 60% : 40%. The treatment was repeated 3 times to get 18 units of the experiment. The data obtained from the result research were analyzed by variance and if the treatment had an effect on the variable then continued with Duncan test. The results showed that the ratio of pumpkin flour and mocaf had significant effect on water and ash content, total carotenoid, unfolding factor, hedonic test (colour, aroma, texture, taste, pores uniformity and overall acceptance), and scoring test (colour, aroma, taste, pores uniformity) of chiffon cake. Ratio of 30% pumpkin flour : 70% mocaf has the best characteristic with 36.65% water content, 1.38% ash content, 511.65% unfolding factor, 27.39 ?g/g total carotenoid, pores uniformity is uniform and liked, color yellow and liked, flavor pumpkin medium and rather liked, texture soft and liked, taste rather typical pumpkin and liked and overall acceptance liked.